Investigating the Role of Anesthesia Technicians in Promoting Safe Medication Practices and Preventing Medication Errors in the Operating Rooms of Hafr Al-Batin Hospitals: A Qualitative Study - Seadoun Raheel N Aldhafeeri,; Mashref Ytaim R Aldhafeeri,; Meshari Tuwayrish Shnan Alshammari,; Faris Aiydh M Alanazi,; Fahad Eissa Alanazi,; Omar Abdullah W Aloslib, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Medication errors in the operating room can have severe consequences for patient safety. Anesthesia technicians play a crucial role in promoting safe medication practices and preventing medication errors. This qualitative study aims to investigate the role of anesthesia technicians in promoting safe medication practices and preventing medication errors in the operating rooms of Hafr Al-Batin hospitals. Semi-structured interviews were conducted with 20 anesthesia technicians purposively selected from three hospitals in Hafr Al-Batin. Thematic analysis was used to identify key themes and subthemes. The findings revealed that anesthesia technicians contribute to safe medication practices through their roles in medication preparation, double-checking, and communication with the anesthesia team. They also identified challenges such as workload, distractions, and inadequate training that may hinder their ability to prevent medication errors. The study highlights the importance of recognizing and supporting the role of anesthesia technicians in promoting patient safety in the operating room. Recommendations include providing targeted training, fostering a culture of safety, and improving communication and collaboration among the anesthesia team.